THE LIFE AND CREATIVE HERITAGE OF UBAYDULLOH ALAMKASH - Sanaqulboyev Inombek (Prospects for innovative technologies in science and education, 2026)
This article examines the life and multifaceted creative heritage of Ubaydulloh Islom so‘fi o‘g‘li, widely known by the pen name Alamkash (1845–1925). The study explores his major contributions to Eastern literature, including the "Devoni Alamkash" (The Divan of Alamkash), "Bayozi Alamkash" (The Anthology of Alamkash), and his educational works such as "Hisob kitobi" (The Book of Calculation) and the translation of "Chor kitob" (The Four Books). The article also highlights contemporary scholarly perspectives from researchers such as A. Saidov, P. Turopova, and I. Suvonqulov, emphasizing Alamkash’s role in preserving Sufi traditions and the literary environment of the Jizzakh region during a period of significant political transition.